2017
DOI: 10.1016/j.aogh.2017.03.189
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Occupational Injuries among Building Construction Workers in Kampala City, Uganda

Abstract: Background: About 1,000 people die and close 860,000 people sustain injury at work daily globally. Health and safety improvement requires strong evidence, but most studies focus on general causes. This study assessed individual, work environment and behavioral determinants of occupational injuries among building construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
3
3
1
Order By: Relevance
“…The result is in line with the study conducted in Addis Ababa and Uganda i.e. 34.6% [10] and 32.4% [11] respectively. This consistency might be due to the prevention strategies and economic development of the countries.…”
Section: Discussionsupporting
confidence: 90%
“…The result is in line with the study conducted in Addis Ababa and Uganda i.e. 34.6% [10] and 32.4% [11] respectively. This consistency might be due to the prevention strategies and economic development of the countries.…”
Section: Discussionsupporting
confidence: 90%
“…Weights are from the random-effects model Note. Weights are from the random-effects model Journal of Environmental and Public Health and Uganda (32.4%) [27]. e finding is in line with study from Egypt (46.2%) [28] and Ghana (57.91%) [25].…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, workers engaged in the work by wearing personal protective equipment were 2.32 times less likely to develop occupational injury than those workers who did not use PPE. e finding of this study was supported by studies performed in Mumbai, India, and Kampala City, Uganda, which indicated that the use of PPE in a working environment reduces the occurrence of occupational injuries [27,29].…”
Section: Discussionsupporting
confidence: 74%
“…The result of this study is lower than the results of other studies in Addis Ababa, 84.7% [31] and 67.7% [39], Iran, 79.8% [40]; Tamil Nadu, 44.3% [41]; and Egypt, 46.2% [42]. The result of this study is also higher than the report of other studies in Gondar, 15% [43]; Uganda, 32.4% [44]; and China 34.82% [45]. This difference might be due to differences in study settings, working conditions, level of accident prevention strategies, and socio-cultural and regulatory factors.…”
Section: Discussioncontrasting
confidence: 72%